2013
DOI: 10.1007/s13277-013-1309-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of onco and tumor suppressor MiRNAs by mTORC1 inhibitor PRP-1 in human chondrosarcoma

Abstract: Metastatic chondrosarcoma of mesenchymal origin is the second most common bone malignancy and does not respond either to chemotherapy or radiation; therefore, the search for new therapies is relevant and urgent. This study aimed to reveal the comparative analysis of miRNAs and their targets in human JJ012 chondrosarcoma cell line between control and experimental samples, treated with mTORC1 inhibitor, cytostatic antiproliferative proline-rich polypeptide (PRP-1). Examination of tumor-specific microRNA expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…The upregulation of SOCS3, TET1 and TET2 expression in a dose-dependent manner by PRP-1 further demonstrates the ability of this cytokine peptide to upregulate tumor suppressor genes in general (8)(9)(10). Even though PRP-1 did not exert any effect on tumor suppressors or oncoproteins of the Hippo or Hedgehog signaling pathways, there was an important conclusion to consider: The inhibition of tumor suppressors by PRP-1 depends on the pathway these tumor suppressors represent or are involved in.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The upregulation of SOCS3, TET1 and TET2 expression in a dose-dependent manner by PRP-1 further demonstrates the ability of this cytokine peptide to upregulate tumor suppressor genes in general (8)(9)(10). Even though PRP-1 did not exert any effect on tumor suppressors or oncoproteins of the Hippo or Hedgehog signaling pathways, there was an important conclusion to consider: The inhibition of tumor suppressors by PRP-1 depends on the pathway these tumor suppressors represent or are involved in.…”
Section: Discussionmentioning
confidence: 92%
“…The effect of the mammalian target of rapamycin complex 1 (mTORC1) inhibitor and anti-proliferative immunomodulator, proline-rich polypeptide 1 (PRP-1) (3-7), on the expression of cytokines, tumor suppressors SOCS3, TET1/2 and oncoproteins of inflammatory oncogenic pathways, including the Hedgehog and Hippo pathways, was also investigated. PRP-1 is a powerful upregulator of tumor suppressor microRNAs (miRNAs) and proteins, and a downregulator of oncoproteins, as reported in previous publications from our laboratory (8)(9)(10). Ten eleven translocation (TET) enzymes, a family of α-ketoglutarate (α-KG)-dependent dioxygenases, catalyse the oxidative reactions of 5-methylcytosine (5mC) to promote the DNA demethylation process.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Cytostatic PRP-1 manifests its antiproliferative effect via cell cycle regulation in cancer (10), as well as by its unique ability to upregulate tumor suppressor proteins (26) and micro RNA (miR) tumor suppressors (miR20a, miR125b and miR192) while causing downregulation of onco-miRs (miR509-3p, miR589, miR490-3p and miR 550) in the human chondrosarcoma cell line, JJ012 (27), demonstrating the possibility for future therapeutic interventions.…”
Section: Neuropeptides Involved In Epigenetic Control Of Cancermentioning
confidence: 99%
“…The first significant study of miRNAs in chondrosarcoma tissue samples and cell lines revealed downregulation of let-7a, miR-100, miR-136, miR-222, miR-335, and miR-376a compared to normal chondrocytes (Yoshitaka et al, 2013; Nugent, 2014). Another recent study shows that overexpressing proline-rich polypeptide (PRP-1) inhibited mTORC1, which resulted in upregulation of certain tumor suppressor miRNAs (miR-125b, miR-192) and downregulation of oncomiRs (miR-550, miR-589, miR-490-3p) (Galoian et al, 2014). Similarly, another study demonstrated that overexpression of miR-518b decreased the expression of Bcl-2, which is an anti-apoptotic that led to increased expression of Bax, a pro-apoptotic in human chondrosarcoma cell lines (Liang et al, 2014).…”
Section: Chondrosarcomamentioning
confidence: 99%